Measles in Scotland, 2013. Issue 1 (February 2014) - Pollock, K; Potts, A; Love, J; Steedman, N; Donaghy, M
In 2013, Wales and England experienced large outbreaks of measles, a disease that has been targeted by the World Health Organisation for European elimination by 2015. Unfortunately, measles-mumps-rubella vaccine uptake declined to less than 80% in Wales and England after the Wakefield publicity and this resulted in increased population susceptibility to measles. In Scotland, measles-mumps-rubella vaccine uptake dropped to 87% in 2003. Scottish public health efforts in response to this decline aimed to maximise uptake of MMR1 by two years; ensure at least 95% uptake of one dose of measles-mumps-rubella before starting school at age five; and maximise uptake of the second dose of measles-mumps-rubella by age six. Although Scotland has not had any large outbreaks reported to date, transmission of measles from healthcare workers to patients has occurred and reiterates the importance of all healthcare workers accurately knowing their immune status and, when needed, to be fully immunised.